2019
DOI: 10.1159/000496462
|View full text |Cite
|
Sign up to set email alerts
|

Mask versus Prongs for Nasal Continuous Positive Airway Pressure in Preterm Infants: A Systematic Review and Meta-Analysis

Abstract: Nasal continuous positive airway pressure (NCPAP) is an effective method of respiratory support for preterm infants. Nasal masks and binasal prongs are two interfaces available to deliver NCPAP, and it is unclear if one is superior to the other. We conducted a systematic review and meta-analysis, using the methodology recommended by the Cochrane Collaboration, to compare the efficacy and safety of nasal masks versus binasal prongs to deliver NCPAP in preterm infants <37 weeks of gestation. Ovid MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…Short binasal prongs or nasal masks are the recommended interface when providing CPAP to infants 21 22. Several other interfaces are widely used for CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Short binasal prongs or nasal masks are the recommended interface when providing CPAP to infants 21 22. Several other interfaces are widely used for CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 Systematic reviews and meta-analyses of these clinical trials showed a similar benefit of reduced risk of intubation when NCPAP is provided with nasal masks compared with binasal prongs. [2][3][4] Nonetheless, these systematic reviews suffered significant limitations due to imprecision resulting from the small sample size of the clinical trials and the inability to blind the intervention. [2][3][4] As it is impractical to blind the intervention in clinical trials, the possible way to improve the certainty in the evidence is by enhancing the precision.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Nonetheless, these systematic reviews suffered significant limitations due to imprecision resulting from the small sample size of the clinical trials and the inability to blind the intervention. [2][3][4] As it is impractical to blind the intervention in clinical trials, the possible way to improve the certainty in the evidence is by enhancing the precision. Hence, we undertook this systematic review to identify whether the confidence in the estimate can be improved by including the additional clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of nasal injury associated with NCPAP ranges from 6.4% to 91.6% [ 36 , 46 , 48 ] and is inversely related to the gestational age and birth weight [ 46 ]. Numerous RCTs and meta-analyses have demonstrated an association between the type of interface and nasal injury during noninvasive ventilation [ 48 51 ]. Short binasal prongs and nasal masks are the most widely used interfaces, but nasopharyngeal tube and nasal cannula have also been utilised [ 29 , 52 54 ].…”
Section: Complications Of Ncpapmentioning
confidence: 99%
“…The merits and demerits of these interfaces are shown in Table 2 . Nasal mask is generally associated with a significantly lower risk of nasal injury compared to binasal prongs [ 48 51 ]. Nasal masks apply excessive constant pressure to the nasal bridge and philtrum, reducing local tissue perfusion and causing nasal injury [ 50 ].…”
Section: Complications Of Ncpapmentioning
confidence: 99%